PROPOSING AWQAF ALTERNATIVE PLAN (AAP): THE WAY FORWARD & SUSTAINABLE HIGHER EDUCATION FINANCIAL SYSTEM - Anwar Allah Pitchay; Mohd Najwadi Yusoff Abdul Rahman; Mohamed Asmy Mohd Thas Thaker; Zubir Azhar; Al Amin Mydin; Mohamad I’sa Abd Jalil (Universitas Muhammadiyah Yogyakarta, 2018)
The future direction of the public university is to self-sustained due to the inconsistency of the national economic growth. For example, reduced in the national income has forced the Malaysian government to cut the allocation of funds to various ministries’ in 2016 compared to 2015 budget. The consequences of this phenomenon the government has reduced the allocation of budget to Ministry of Higher Education, which is cut by RM2.4 billion, from RM15.78 billion in 2015 compared to RM13.37 billion in 2016. This scenario has imposed various challenges to many public universities’ management to manage university expenses and explore new avenue to generate income. There are various ways to generate income and we find most of the tertiary education in Malaysia is not able to practice effective management especially in managing the cost of organizing a program. For example, food and beverages (FB) spend by the university during events are not effective and most of the time is wasted. This argument is developed based on the observation and also supported by an informal interview with a vice-chancellor (VC) of one of the public university in Malaysia. The VC do agree that the university management needs to find a solution to overcome the issue of wastage due to the forecasted cost rather than an accurate cost to organize a university’s events. Therefore, we believe that the main issue faced the university’s management is to identify an exact number of participants and etc. Thus, the current practice is based on the forecasted estimation rather than accurate estimation. Therefore, to solve this problem, the present study aims to provide an opportunity to the tertiary education in Malaysia which able to estimate an accurate cost and at the same time able to create waqf fund using effective fund management approach by proposing awqaf alternative plan (AAP) model. The proposed model is expected to generate Waqf fund and eliminate wastage management practice.